GOVERNMENT DEBT AND BANKING FRAGILITY: THE SPREADING OF STRATEGIC UNCERTAINTY. (6th July 2018) - Cooper, Russell; Nikolov, Kalin
Abstract: This article studies the interaction of government debt and financial markets. This interaction, termed a "diabolic loop, " is driven by government choice to bail out banks and the resulting incentives for banks to hold government debt instead of self‐insure through equity buffers. We highlight the role of bank equity issuance in determining whether the "diabolic loop" is a Nash equilibrium of the interaction between banks and the government. When equity is issued, no diabolic loop exists. In equilibrium, banks' rational expectations of a bailout ensure that no equity is issued and the sovereign‐bank loop is operative.